IMPLEMENTASI PEMBERDAYAAN MASYARAKAT DAN KAPASITAS AKTOR PERGURUAN TINGGI DI KOTA SERANG - Ahmad Sururi; Budi Hasanah; Mayu Ma’lumatiyah; Annisa Dwianti (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
The implementation of community empowerment has yet to provide a fully sustainable impact. In practice, it still uses the paradigm of tertiary institutions empowering the community and not universities together with the community to empower. This study aims to analyze how the implementation of community empowerment and the capacity of higher education actors are analyzed based on the stages of community empowerment, including planning, objectives, strategies, operational areas, and impact evaluation. This research method uses a qualitative approach through a case study at the University of Serang Raya. Data collection techniques using observation and interviews and data analysis using a data reduction approach, data presentation, and conclusion. The study results show that the implementation of community empowerment and the capacity of higher education actors has been running effectively. Research findings indicate that sustainable impact evaluation requires consistency in community empowerment and encourages innovative approaches to sustainable community empowerment models, monitoring and strengthening based on community participation and placing communities as crucial actors and innovative approaches to empowerment.